VERBA BERPREPOSISI DALAM BAHASA INDONESIA - -, Suhardi (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2005)
A verb with a preposition here refers to a verb with apreposition following it in use. So a verb to be used that way differsfrom a verb phrase; the latter consists of one main element with atleast one other element added to it while the former consists of a verband a preposition with neither being a main element nor an addedelement. Therefore, a verb phrase is endocentric in nature while averb with a preposition is exocentric in nature.A verb with a preposition can be with or without an affix.The affixes commonly used in such verbs are, among others, ber-,ber-an, and ber-kan (as used in, for example, berfungsi sebagai,berkenaan dengan, and berdasarkan atas); di-, di-kan, di-i, anddiper-kan (as used in, for example, dibagi atas, diarahkan kepada,diikuti oleh, and dipergunakan sebagai); me(N)- (as used in, forexample, mengarah pada and mengacu ke); and ter- and ter-kan (asused in, for example, tergantung pada, terdiri atas, and terbedakandari). Meanwhile, the prepositions used with such verbs can be (1)single prepositions without affixes (such as, di, ke, dari, pada, atas,and dengan) or with affixes (such as, sebagai, terhadap, menjadi,and mengenai) or (2) combined prepositions used side by side (suchas, kepada, daripada, ke dalam, and di dalam) or in pairs (such as,antara dan ...; antara dengan ...; and dari hingga ...). In addition,the presence of some prepositions after some verbs (as that in, forexample, berkembang menjadi and berdomisili di) is obligatorywhile that of some other prepositions after some other verbs (as thatin, for example, berbicara tentang, dihadiri oleh, and terdiri atas/dari) is optional.Keywords: verb, preposition, verb with preposition